2020
DOI: 10.33019/equity.v8i1.14
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kemiskinan Dan Pendidikan Terhadap Kesehatan Masyarakat

Abstract: Pertumbuhan ekonomi dapat mengurangi tingkat kemiskinan pada suatu negara. Penelitian ini bertujuan untuk menganalisis pengaruh kemiskinan dan pendidikan terhadap kesehatan masyarakat. Analisis dalam penelitian ini menggunakan data sekunder yang bersumber pada BPS dengan jumlah data sebesar 63 sampel yang terdiri dari data kemiskinan, rata-rata lama sekolah dan kesehatan masyarakat tahun 2010-2018. Penelitian ini menggunakan analisis regresi berganda dengan angka harapan hidup sebagai variabel dependen dan rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…It means that when poverty is high, life expentancy district or city in Central Kalimantan Province actually decrease, and vice versa. The results of this study support (Azahari, 2020) that poverty shows a negative relationship to health, but statistically insignificant, thus there is no effect of poverty on the health of the people of Bangka Belitung Islands Province. Similar results were described by (Bariyah, 2022) who found that there was no correlation between poverty and life expectancy (LE) in West Kalimantan Province.…”
Section: Results Correlation Testsupporting
confidence: 71%
See 1 more Smart Citation
“…It means that when poverty is high, life expentancy district or city in Central Kalimantan Province actually decrease, and vice versa. The results of this study support (Azahari, 2020) that poverty shows a negative relationship to health, but statistically insignificant, thus there is no effect of poverty on the health of the people of Bangka Belitung Islands Province. Similar results were described by (Bariyah, 2022) who found that there was no correlation between poverty and life expectancy (LE) in West Kalimantan Province.…”
Section: Results Correlation Testsupporting
confidence: 71%
“…Life expentacy is one of the indicator captured quality of health, it is on of key metrics for assessing population health and hence, of primary interest in medical research (Aanegola et al, 2022). This statement is supported by (Azahari, 2020) that poverty has a negative correlation with public health, meaning that when poverty increases, it can reduce health, especially the life expectancy of an individual. Then education is positively correlated with public health, meaning that when educational indicators increase it can extend the life expectancy of an individual.…”
Section: Introductionmentioning
confidence: 99%
“…Neglect of the education and health care of farm family member's results in reduced productivity, so poverty will continue to surround the farm family. Azahari (17) argues that poverty has a negative influence on public health, namely reducing the realization of public health figures, in particular the life expectancy of an individual. While education has a positive impact on public health, this means that increasing educational factors can improve public health indicators in this case the life expectancy of individuals.…”
Section: Poverty Among Forest Farmer Householdsmentioning
confidence: 99%